2020
DOI: 10.35848/1347-4065/ab709d
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary switching of ReRAM investigated by in-situ TEM

Abstract: The filament operation of resistive random-access memory (ReRAM) was studied via in-situ transmission electron microscopy (in-situ TEM), and the contribution of the conductive filament to the resistance switching was experimentally confirmed. In addition to the operation principles, the device degradation mechanism was studied through repeated write/erase operations. The importance of controlling Cu movement in the switching layer was confirmed for stable CBRAM (conductive bridge random access memory) operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
(181 reference statements)
0
6
0
Order By: Relevance
“…[34][35][36] This high degree of crystallinity shows high mobility of Ag + species within the switching layer, forming percolation paths for the formation and rupture of the filament during the repeated ON/OFF cycle. [35][36][37][38][39][40] EDX scan and mapping are conducted on the cross-sectioned samples to confirm the chemical information of the conducting filament. Figure S6 in the supplementary material shows the crosssectioned TEM EDX scan mapping of the filament region of sample C. It is important to note that the W signal remains stable and uniform throughout the sample.…”
Section: Articlementioning
confidence: 99%
“…[34][35][36] This high degree of crystallinity shows high mobility of Ag + species within the switching layer, forming percolation paths for the formation and rupture of the filament during the repeated ON/OFF cycle. [35][36][37][38][39][40] EDX scan and mapping are conducted on the cross-sectioned samples to confirm the chemical information of the conducting filament. Figure S6 in the supplementary material shows the crosssectioned TEM EDX scan mapping of the filament region of sample C. It is important to note that the W signal remains stable and uniform throughout the sample.…”
Section: Articlementioning
confidence: 99%
“…The fundamental mechanism for the transition between the high‐resistive state (HRS) and low‐resistive state (LRS) in ReRAM cells is the nanoscale redox reaction involving oxygen ion migration. [ 7–15 ] Redox reactions are observed in various oxides that can be handled in a process compatible with existing semiconductor technologies, which support the practical application and commercialization of ReRAM. [ 16 ] One of the advantages of resistance changes in ReRAM is the high resistance change ratio, and it is possible to control the resistance change in an analog manner.…”
Section: Introductionmentioning
confidence: 97%
“…The fundamental mechanism for the transition between the high-resistive state (HRS) and low-resistive state (LRS) in ReRAM cells is the nanoscale redox reaction involving oxygen ion migration. [7][8][9][10][11][12][13][14][15] Redox low temperature to room temperature. The temperature dependence of the noise spectra at given frequencies revealed that multiple trap levels exist and that they are related to the electrical resistance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The device for RRAM operates via the resistive switching of the MIM structure between a high-resistance state (HRS) and a low-resistance state (LRS) using the formation and rupture of conducting filaments or the modulation of the oxide−metal interface. 1 To date, the performance of oxide-based RRAM has been substantially improved using various materials such as HfO 2 , 2 Al 2 O 3 , 3 TiO x , 4,5 ZnO, 6 CeO 2 , 7 and Fe 2 O 3 . 8 In particular, filament-based switching devices are classified as valence change memory (VCM) or conductive-bridge random access memory (CBRAM) devices depending on whether the filament is composed of oxygen vacancies (V o ) or metal cations generated from active electrodes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The device for RRAM operates via the resistive switching of the MIM structure between a high-resistance state (HRS) and a low-resistance state (LRS) using the formation and rupture of conducting filaments or the modulation of the oxide–metal interface . To date, the performance of oxide-based RRAM has been substantially improved using various materials such as HfO 2 , Al 2 O 3 , TiO x , , ZnO, CeO 2 , and Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%